(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1855)
John Alexander Smith exhibited a rubbing of a sandstone slab found near Newstead and now displayed in Dryburgh Abbey. Dr Smith argues that the trade tools on one side of the slab may indicate that the person the monument was dedicated to may have been a freemason. He also added to the list of Roman coins discovered near Newstead, as detailed in his earlier articles on the subject. Meeting notes for January 23, 1854 are appended.